Interpreting Osteogenesis Imperfecta Variants of Uncertain Significance in the Context of Physical Abuse: A Case Series - Canter, Jennifer; Rao, Vinod B.; Palusci, Vincent J.; Kronn, David; Manaster, Michal; Altman, Robin (Journal of Pediatric Genetics, 2019)
Unexplained childhood fracture(s) warrant consideration of physical abuse and osteogenesis imperfecta (OI). Genetic OI testing may identify “variants of unknown significance (VUS).” Interpretation of VUS in context of potential abuse may have protective, criminal, and medical impacts. This case series explores practices regarding clinicians' interpretation of VUS during child abuse evaluations. Variability was noted regarding factors considered for interpreting clinical significance. Based on these cases, recommendations for careful and thorough evaluation are detailed, including proposed use of a limited follow-up skeletal survey in 3 months, as a consideration to assess healing of prior fractures and to look for any additional injuries.
Keywords: variant of unknown significance; osteogenesis imperfect; child physical abuse